A Stranger Thing? Sweden – The Upside Down of Multilevel Trust - Gissur Ó. Erlingsson (Research Institute of Industrial Economics (IFN), 2020)
There are good reasons to expect that citizens will appreciate local government more than central government. Sure enough, previous studies have found support for this assumption. Nevertheless, I will argue that it is theoretically far too simple to think that decentralization and citizen's proximity to decision-making by definition trumps centralization and distance. As with comparative country studies, institutional quality must be taken into account in analyses of local government and multilevel trust. To illustrate this point, a closer investigation of Sweden - a decentralised, high-trust and low-corruption country - is conducted. Looking back over the past 20 years, and studying several indicators of trust, Sweden turns out to be a curious outlier from the general pattern: Swedes trust municipalities far less than the state. Ex ante, these findings are puzzling. To make them intelligible, while at the same time aiming to contribute to a more nuanced understanding of multilevel trust, I argue that the unfortunate combination of three factors have brought about this curious circumstance: 1) the far-reaching decentralisation and principal role Swedish municipalities have successively been given in implementing assignments which lie at the heart of Swedish welfare state policies; 2) that several of the municipalities' assignments are particularly susceptible to corruption; and 3) that the increase in responsibilities as well as the increased danger zones for corruption has not been accompanied by institutions that ensure transparency and checks-and-balances in local government, ultimately leaving Swedish local government with institutions that obfuscate accountability.
Keywords: D02; H70; 330; Trust; Multi-level trust; Accountability; Impartiality; Corruption; Local government; Decentralisation; Sweden